Two new and distinct roles for Drosophila Argonaute-2 in the nucleus: alternative pre-mRNA splicing and transcriptional repression - Taliaferro, J. Matthew (Cold Spring Harbor Laboratory Press, 2013)
Transcription and pre-mRNA alternative splicing are highly regulated processes that play major roles in modulating eukaryotic gene expression. It is increasingly apparent that other pathways of RNA metabolism, including small RNA biogenesis, can regulate these processes. However, a direct link between alternative pre-mRNA splicing and small RNA pathways has remained elusive. Here we show that the small RNA pathway protein Argonaute-2 (Ago-2) regulates alternative pre-mRNA splicing patterns of specific transcripts in the Drosophila nucleus using genome-wide methods in conjunction with RNAi in cell culture and Ago-2 deletion or catalytic site mutations in Drosophila adults. Moreover, we show that nuclear Argonaute-2 binds to specific chromatin sites near gene promoters and negatively regulates the transcription of the Ago-2-associated target genes. These transcriptional target genes are also bound by Polycomb group (PcG) transcriptional repressor proteins and change during development, implying that Ago-2 may regulate Drosophila development. Importantly, both of these activities were independent of the catalytic activity of Ago-2, suggesting new roles for Ago-2 in the nucleus. Finally, we determined the nuclear RNA-binding profile of Ago-2, found it bound to several splicing target transcripts, and identified a G-rich RNA-binding site for Ago-2 that was enriched in these transcripts. These results suggest two new nuclear roles for Ago-2: one in pre-mRNA splicing and one in transcriptional repression.